PENGARUH LUAS LAHAN, TENAGA KERJA, PENGGUNAAN BENIH, DAN PENGGUNAAN PUPUK TERHADAP PRODUKSI PADI DI JAWA TENGAH - Ludfil Khakim; Dewi Hastuti; Aniya Widiyani (MEDIAGRO, 2013)
Paddy production is influenced by several factors, including land, labor, seed and fertilizer use. This study aims to determine the effect of production inputs (land, labor, seeds, and fertilizers) on rice production in Central Java. Secondary data from 35 regency in Central Java Province over the past five years have been analyzed to answer the research objectives. Analysis tool used is multiple regression with Coob-Douglas production function. The analysis showed that the independent variables consist of land, labor, seed and fertilizer together had a significant effect on paddy production in Central Java Province at the level of confidence up to α = 99% (F test). Test coefficient of determination (R2) of 0,924, so the variation of variables in paddy production in Central Java can be explained by the variables of land, labor, seed and fertilizer by 92,4% while the remaining 7,6% is explained by other factors outside the model. Partially based on the t test, land, labor and fertilizer effect is significant at p <0,01, while the use of the seeds have a significant effect at α =  10 %. The entire independent variables have a positive and significant at p <0,01 - p <0,10 for the hypothesis 1, 2, 3, and 4 are acceptable. Production elasticity value is 1,426 (elastic). This means that the overall paddy production in Central Java is still able to operate with increasing returns to scale. Key word: Central Java, input, paddy, production, scale of return.